The effect of new anti-adhesive and antibacterial dental resin filling materials on gingival fibroblasts. Issue 9 (September 2021) - Landenberger, Philipp; Baumann, Linn; Gerhardt-Szép, Susanne; Rüttermann, Stefan
Highlights: Secondary caries is the main reason for failure of composite fillings. New antibacterial composites have proven to modify biofilm formation in qualitative and quantitative ways. New antiadhesive composites have shown to diminish bacterial adhesion. Biocompatibility was tested using LDH, BrdU, MTT, TGF-ß1, IL-8. Antibacterial composites damage human gingival fibroblasts; antiadhesives do not. Abstract: Objective: Aim of this study was to evaluate the biocompatibility of four experimental antiadhesive and antibacterial dental filling composites on human gingival fibroblasts (HGFs). Methods: For these experimental resin composites a delivery system based on novel polymeric hollow beads, loaded with Tego Protect (Aa1), Dimethicone (Aa2), Irgasan (Ab1) and methacrylated polymerizable Irgasan (Ab2) as active agents was used. The cultured HGFs' cell integrity, proliferation, viability, collagen synthesis and cytokine release were measured. For this purpose, human gingival fibroblasts were treated with eluates from all four composites and compared with an experimental standard composite (ST). Eluate extraction times 24 h and 168 h were chosen. Results: Statistical analysis was conducted via a mixed model. Both antibacterial composites reduced proliferation, collagen and cytokine synthesis significantly (p < 0.05), increasing with time of elution. Ab1 did also have a damaging effect on the membrane and on cell viability. Significance: Overall, it can be concluded that the antiadhesive composites showed clear advantages over the antibacterial composites in terms of biocompatibility. This study also continues to show the potential of the new poly-pore system, as it can be used for a variety of other applications in future composite mixtures.